2020
DOI: 10.1186/s13244-020-00936-w
|View full text |Cite
|
Sign up to set email alerts
|

The 100 top-cited meta-analyses of diagnostic accuracy in radiology journals: a bibliometric analysis

Abstract: Purpose To identify the 100 top-cited meta-analyses of diagnostic accuracy studies published in radiology, medical imaging and nuclear medicine journals. Methods A PubMed search with pre-defined criteria was performed. The 100 top-cited articles meta-analyses were retrieved, using a custom Python script and the Scopus Application Programming Interface (Elsevier). Publication, citation and affiliation details were extracted from each meta-analysis. No formal statistical analysis was performed. Results The top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…The number of citations has still been used as a reliable objective marker of the quality and impact of a paper; it is variable in different subdisciplines and depends on the size of the field of study. In our data, the number of citations times of the top 100 cited original articles and reviews is 131 to 1,144, with a total cited of 25,723; it is lower than some hot research fields such as lncRNAs (15) and neuro-interventional (16) but higher than that of a meta-analysis of radiology (17), suggesting that PPGL research worldwide was in a tepid period. The PPGL research field was still not prominent enough in the world.…”
Section: Discussionmentioning
confidence: 52%
“…The number of citations has still been used as a reliable objective marker of the quality and impact of a paper; it is variable in different subdisciplines and depends on the size of the field of study. In our data, the number of citations times of the top 100 cited original articles and reviews is 131 to 1,144, with a total cited of 25,723; it is lower than some hot research fields such as lncRNAs (15) and neuro-interventional (16) but higher than that of a meta-analysis of radiology (17), suggesting that PPGL research worldwide was in a tepid period. The PPGL research field was still not prominent enough in the world.…”
Section: Discussionmentioning
confidence: 52%
“…This study had several limitations. The search strategy was specific to the 40 highest impact medical imaging journals . Therefore, relevant imaging DTA meta-analyses published in other journals may have not been captured, resulting in our cohort of 242 included studies not being fully representative of work published in nonmedical imaging or lower impact factor journals.…”
Section: Discussionmentioning
confidence: 99%
“…Among the imaging modalities used in the studies, CT, PET-CT and radiomics were predominant. The increasing use of PET-CT for cancer staging, technological advances in PET-CT imaging and the discovery of new radiotracers, and clinical use of hybrid and molecular imaging modalities reflect the growing interest in PET-CT (25)(26)(27)(28). In Liang et al's (24) literature analysis, radiomics were reported to be promising for lung cancer.…”
Section: Discussionmentioning
confidence: 99%